Proceedings of the 1st Workshop on Embodied Interaction With Smart Environments 2016
DOI: 10.1145/3008028.3008029
|View full text |Cite
|
Sign up to set email alerts
|

Exploring self-interruptions as a strategy for regaining the attention of distracted users

Abstract: In this paper we present a first exploratory study investigating the effects of a contingently self-interrupting vs nonself-interrupting virtual agent in a smart home environment who transmits information to a human interaction partner. We tested the hypothesis that self-interruptions are a strategy for keeping the user's attention, as measured by postinteraction information recall. Interestingly, our experiment does not allow us to confirm this hypothesis. In fact, users found the self-interruption strategy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Additionally, (3) this additional information allows the monitoring of the interaction partner. In order to have a meaningful interaction, a good deal of different feedback information should be taken into account [25]-whether to verify that the interaction partner understood the current dialogue act or to be able to react on a distracted interaction partner [26]. Feedback signals, such as gazing behaviour, head nods, and verbal backchannels allow the system further insight into the mental states of the user.…”
Section: Situated Dialoguementioning
confidence: 99%
“…Additionally, (3) this additional information allows the monitoring of the interaction partner. In order to have a meaningful interaction, a good deal of different feedback information should be taken into account [25]-whether to verify that the interaction partner understood the current dialogue act or to be able to react on a distracted interaction partner [26]. Feedback signals, such as gazing behaviour, head nods, and verbal backchannels allow the system further insight into the mental states of the user.…”
Section: Situated Dialoguementioning
confidence: 99%
“…[22] found that users prefer a system that deploys fillers, while [20,23] explicitly point out difficulties of filler synthesis compared to other hesitation types. Lengthening and silence fare well in terms of user feedback in offline evaluation studies [23], but embedded in a smart-home scenario, systems that hesitate only by means of silence are perceived as less friendly than non-hesitating systems [24,25]. For the purposes of this study, we focus on lengthening as a marker of hesitation and uncertainty.…”
Section: Background and Overviewmentioning
confidence: 99%
“…Here we define attention as a state in which the VFoA matches with current focus of discourse (FoD)(cf. [6]). Incremental processing capabilities.…”
Section: Requirements and Implementationmentioning
confidence: 99%
“…[4] with a forecasting model of disengagement lead to less costly disengagement management, but no evaluation of the effect on the human interaction partner, e.g., on task performance or subjective rating of the robot are conducted. [6,7] evaluated self-interruptions in an smart-home setting. The authors use silence as an attention-regaining strategy whenever the attention of the human interaction partner moves away.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation